Paramedics and EMTs perceptions of geriatric trauma care - Fahad Ghazi Bander Al-Hantoshi,; Ibrahim Shihan Marzen Alotaibi,; Abdullah Dughaylib Alotaibi,; Waleed Ali Alzahrani,; Hassan Mohammad Hassan Alyami,; Ibrahim Rashed Ali Alkhamisi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The aging of the Saudi Arabia population is expected to have a significant impact on the number of emergency medical services (EMS) for older adults. The occurrence of trauma has identified that 62% of the persons over the age of 65 fall annually. EMS personnel are often the first healthcare professionals to provide care at the patients' residence. Given the increased demand for training in the care of older adults, the low rates of providing pre-hospital analgesia services to injured older adults, the long-term deficits that can occur in the elderly due to poor outcomes, and finally the poor expertise in fall risk assessment and follow-up, there are concerns about EMS practitioners' ability to deliver the specialized care necessary for the elderly. The higher number of hospitalizations, longer and slower healing times, and increased susceptibility to wounds in older patients all contribute to their higher rates of complications, morbidity, and mortality. In order to prepare for the rise in the numbers of elderly, EMS programs and activities should focus on: pre-hospital care buffers, long-term population health and well-being, and patient family involvement. In an effort to improve the patient-centered fall care model, this paper examines the views of EMS practitioners concerning the provision of geriatric pre-hospital trauma care. The findings of this comprehensive study reveal that both paramedics and EMTs have varying and distinct perceptions regarding the numerous challenges and subtle nuances involved in providing effective trauma care specifically to geriatric patients in need.